Research Metrics for Health Science Schools: A Conceptual Exploration and Proposal - Gemechu, Nigussie; Werbick, Meghan; Yang, Michelle; Hyder, Adnan A. (Frontiers in Research Metrics and Analytics, 2022)
Research is a critical component of the public health enterprise, and a key component of universities and schools of public health and medicine. To satisfy varying levels of stakeholders in the field of public health research, accurately measuring the return on investment (ROI) is important; unfortunately, there is no approach or set of defined metrics that are universally accepted for such assessment. We propose a research metrics framework to address this gap in higher education. After a selected review of existing frameworks, we identified seven elements of the generic research lifecycle (five internal to an institution and two external). A systems approach was then used to broadly define four parts of each element: inputs, processes, outputs, and outcomes (or impacts). Inputs include variables necessary to execute research activities such as human capital and finances. Processes are the pathways of measurement to track research performance through all phases of a study. Outputs entail immediate products from research; and outcomes/impacts demonstrate the contribution research makes within and beyond an institution. This framework enables the tracking and measurement of research investments to outcomes. We acknowledge some of the challenges in applying this framework including the lack of standardization in research metrics, disagreement on defining impact among stakeholders, and limitations in resources for implementing the framework and collecting relevant data. However, we suggest that this proposed framework is a systematic way to raise awareness about the role of research and standardize the measurement of ROI across health science schools and universities.